Terapia fotobiomoduladora no manejo metabólico do diabetes mellitus tipo 2: ensaio clínico randomizado - OLIVEIRA, Andressa Jhulier Faiola (2024)
The aim of this study was to analyse the effect of different protocols of modified intravascular laser irradiation of blood for the metabolic management of type 2 diabetes mellitus. This is a randomised clinical trial. The sample consisted of 39 participants, 20 in Intervention Group 1 and 19 in Intervention Group 2. The modified intravascular laser irradiation of blood was applied transcutaneously over the vascular bundle in the region of the radial artery, lasting 30 minutes. In both groups, the duration and number of cycles (three cycles) was the same, but the number of applications was different. In Intervention Group 1, applications were carried out for 10 days (between Monday and Friday), with a break of 23 days between cycles, totalling 30 sessions. In Intervention Group 2, applications were carried out for 5 days, with a break of 23 days between cycles, totalling 15 sessions. Sociodemographic and clinical information was collected, as well as daily assessment measures (blood pressure, capillary glycaemia, oxygen saturation and pulse), laboratory tests (fasting glycaemia, glycated haemoglobin, insulin, fructosamine, Homa index, lipid profile and blood count) and quality of life assessment using the Diabetes-39 questionnaire. Laboratory tests were taken at three different times: at the beginning (S1), at the end of the first cycle (S9/S4) and at the end of the intervention (S30/S15), with the exception of glycated haemoglobin, which was only taken at the beginning and end of the intervention. Statistical analyses used 95% confidence intervals and a significance level of p < 0.05. The study was approved by the Ethics Committee (opinion 6.088.755) and registered with the Brazilian Registry of Clinical Trials. The study sample was homogeneous between the groups, with the majority being women (84.6%), married or in a stable union (61.5%), brown (56.4%) and with incomplete primary education (30.7%). The average age was 56.5 years for Intervention Group 1 and 53.8 years for Intervention Group 2. There was an improvement in quality of life in Intervention Group 1, with statistical significance at different collection times. In daily measurements, there was a statistically significant reduction in both groups in blood pressure, capillary glycaemia and pulse; however, only in Intervention Group 2 was there an improvement in lower limb oxygen saturation values. In terms of glycaemic markers, Intervention Group 1 showed a reduction in fasting glycaemia, glycated haemoglobin, insulin, Homa index and an increase in fructosamine (p < 0.05). Intervention Group 2 showed a downward trend in fasting glycaemia and glycated haemoglobin, but an upward trend in fructosamine, insulin and the Homa index; however, these findings were not statistically confirmed. As for the lipid profile and haematological markers, Intervention Group 2 showed a statistically significant reduction in low-density lipoprotein, total cholesterol and total lipids. In this group, the haematological markers erythrocytes and basophils showed an increase (p < 0.05). It is concluded that modified intravascular laser irradiation of blood had a positive effect on glycaemic markers in people with type 2 diabetes mellitus, showing better efficacy when using the protocol in Intervention Group 1. However, the choice of protocol to be used should take into account the desired objective. Participants with an altered lipid profile showed better effects from the modified intravascular laser irradiation of blood using fewer sessions. In addition, in both groups, a statistically significant improvement was seen in insulin values, the Homa index and S%.